Biological uranium (VI) reduction in suspended culture and fixed-media bioreactor systems using indigenous isolates of uranium (VI) reducing bacteria - Chirwa, Evans M.N. (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.